Developing cathode and electrolyte materials for intermediate temperature solid oxide fuel cells - Liu, Tian-Hui (2020)
Solid Oxide Fuel Cells (SOFCs) are one of the most promising energy-conversion technologies due to their high work efficiency (50 - 60%) and fuel flexibility (hydrogen, syngas, biogas etc.). However, the high operating temperature (800 - 1000 °C) of most existing commercial SOFCs induces a number of issues including high manufacturing and operation cost, fast degradation of cell performance, slow start-up and shut-down cycles. Lowering the operating temperature to an intermediate temperature (550 °C - 750 °C) is an effective way to solve these issues. However, reducing operating temperature reduces the electrocatalytic performance of cathode and the oxide ion conductivity for the electrolyte, leading to increased cell internal resistance and reduced power density.